2013
DOI: 10.1214/13-aos1155
|View full text |Cite
|
Sign up to set email alerts
|

Estimating and understanding exponential random graph models

Abstract: 4 The social environment is a pervasive influence on the ecological and evolutionary dynamics 5 of animal populations. Recently, social network analysis has provided an increasingly 6 powerful and diverse toolset to enable animal behaviour researchers to quantify the social 7 environment of animals and the impact that it has on ecological and evolutionary processes. 8 However, there is considerable scope for improving these methods further. We outline an 9 approach specifically designed to model the formation … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
505
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 306 publications
(521 citation statements)
references
References 51 publications
12
505
0
1
Order By: Relevance
“…Another issue that appears in working in coalitional games on the continuum, when coalitions themselves can be a continuum, is avoided in this framework by restricting individuals to form a finite number of links where only the characteristics on the potential connection (and not her identity) matter. 40 The corresponding approximation to dense graphs, known as graphons, is used, for example, by Chatterjee and Diaconis (2013) in their asymptotic study of ERGMs.…”
mentioning
confidence: 99%
“…Another issue that appears in working in coalitional games on the continuum, when coalitions themselves can be a continuum, is avoided in this framework by restricting individuals to form a finite number of links where only the characteristics on the potential connection (and not her identity) matter. 40 The corresponding approximation to dense graphs, known as graphons, is used, for example, by Chatterjee and Diaconis (2013) in their asymptotic study of ERGMs.…”
mentioning
confidence: 99%
“…Many people have delved into this area. A particularly significant discovery was made by Chatterjee and Diaconis [6], who showed that the supremum in (5.16) is always attained and a random graph drawn from the model must lie close to the maximizing set with probability vanishing in n. When β 3 , β 4 ≥ 0, Yin [35] further showed that the 3-parameter space would consist of a single phase with first-order phase transition(s) across one (or more) surfaces, where all the first derivatives of χ exhibit (jump) discontinuities, and second-order phase transition(s) along one (or more) critical curves, where all the second derivatives of χ diverge. The second special situation is when β 3 = 0, Following similar arguments as in Kenyon et al [17], we conclude that d(x) can take only finitely many values.…”
Section: Further Discussionmentioning
confidence: 99%
“…Large deviations techniques are used throughout this paper. We refer the readers to the works of Chatterjee and Diaconis [6] and Chatterjee and Varadhan [7] for more details of this framework.…”
Section: Introductionmentioning
confidence: 99%
“…. , β I ) being a vector of parameters and c β a normalization coefficient; see Chatterjee and Diaconis [8] and references therein. From observed data in the form of a collection of graphs, there are significant challenges to estimate the parameters β.…”
Section: Density Estimation On Graphsmentioning
confidence: 99%
“…From observed data in the form of a collection of graphs, there are significant challenges to estimate the parameters β. In Chatterjee and Diaconis [8], we find an approach that relies on graph limits in the sense of Lovász and large-deviation results for random graphs, and leads to an infinite-dimensional problem whose optimal value is an estimate of the crucial normalization constant c β .…”
Section: Density Estimation On Graphsmentioning
confidence: 99%